Dinâmica populacional da mosca-dos-chifres (Haematobia irritans) em bovinos da raça Guzerá e mestiço em Selvíria, MS - de Almeida, Fabiana Alves [UNESP]; Basso, Fernanda Carvalho [UNESP]; Zocoller Seno, Maria Conceicao [UNESP]; Valerio Filho, Walter Veriano [UNESP] (Universidade Estadual de Londrina (UEL), 2010)
Aiming to know the population dynamics of horn fly on cattle in the municipality of Selviria, MS, Brazil, a study was conducted from March 2004 to June 2005 in the Education, Research and Extension Farm, from Unesp - Campus de Ilha Solteira, located in the municipality of Selviria, MS. It was used IS cows of the Guzera breed and 15 crossbred (Guzera X Holstein-Friesian), respectively 3 and 4 years old, naturally infested. During the experimental period these animals did not receive any insecticide treatment. Visual fly counting by on back region of the animals was carried out at 14 day interval. The horn fly showed two peaks of infestation during the year, one in April and another in October. In the months of highest infestation, the average number of flies did not exceed a 104. The months in which was significant difference between crossbred and Guzera breed was in April, May, August and September 2004 and February, March and April 2005, always with crossbred with higher infestation. In the region studied Haematobia irritans was present throughout the year.
Population dynamics of the horn fly (Haematobia irritans) on Guzera cattle breed and crossbred in Selviria, MS
Keywords: Population dynamics; horn fly; cattle